Canine non‐epitheliotropic CD4‐positive cutaneous T‐cell lymphoma: a case report. Issue 2 (12th December 2018) - Kondo, Hitoshi; Kagawa, Yumiko; Shirota, Kinji; Moore, Peter F.; Nagata, Masahiko
Abstract: A 5‐year‐old, spayed female French Bulldog presented with multiple papules on the skin of the scapular area. Histopathological examination of punch biopsy samples revealed dense infiltration of small lymphoid cells in the superficial dermis and in areas surrounding hair follicles. Immunohistochemical analysis indicated that these cells were positive for CD3, CD4, and TCR αβ, but negative for CD1c, CD8 α, CD8 β, CD11c, CD20, CD45RA, CD90, MHC‐II, and TCR γδ . In addition, CD45 was highly expressed, and the proliferation fraction was very low. Molecular clonality of T‐cell receptor G chains yielded a clonal result. The skin lesions were surgically excised because they had progressed to the lateral front leg. Postoperative clinical course was favorable, and recurrence was not observed until the dog died in a traffic accident, approximately 1 year later. Abstract : This is the first case report describing canine cutaneous CD4‐positive non‐epitheliotropic lymphoma with detailed dermatological features, including clinical course.